Go Ask Your Patients! PSS-QoL Reported Perception of Dryness Correlates With Lacrimal and Salivary Flow in Primary Sjögren's Syndrome - Lackner, Angelika; Bosch, Philipp; Zenz, Sabine; Horwath-Winter, Jutta; Rabensteiner, Dieter Franz; Hermann, Josef; Graninger, Winfried; Stradner, Martin Helmut (Frontiers in Medicine, 2021)
Introduction/Objectives: The patient perspective is an essential outcome parameter in the quest for effective therapy in primary Sjögren's Syndrome (PSS). The EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) is recommended by EULAR to quantify patient's symptom burden and has been used in several clinical trials. Surprisingly, the patient's perception of dryness quantified with ESSPRI does not correlate with objective measures of salivary or lacrimal flow. Thus, we evaluated a newly developed assessment tool-the Primary Sjögren's Syndrome Quality of Life Questionnaire (PSS-QoL)—for quantifying symptoms of dryness in comparison with the ESSPRI and objective measurements of salivary and lacrimal flow. Methods: Data of patients from the PSS registry of the Medical University of Graz fulfilling the 2016 ACR/EULAR classification criteria for PSS were analyzed. The patient perspective was analyzed by PSS-QoL, ESSPRI, Xerostomia Inventory (XI) and Ocular Surface Disease Index (OSDI). Sicca signs were measured with Schirmer's test, unstimulated salivary flow test (USF) and stimulated salivary flow test (SSF). ESSDAI (EULAR Sjögren's Syndrome Disease Activity Index) and EGA (Evaluator Global Assessment, numeric rating scale from 0 to 10) were obtained. In addition, free light chains (FLC) κ and λ, rheumatoid factor (RF) IgM and IgA were determined. Results: Data from 123 PSS patients were analyzed; 91.9% (n = 113) were female, with a mean disease duration of 6.2 (±5.3) years and mean age of 60.1 (±12.4) years. PSS-QoL-dryness revealed significant negative correlations with Schirmer's test (r = −0.31, p < 0.05) and SSF-test (r = −0.390, p < 0.01). In contrast, we found no significant correlation between ESSPRI-dryness and any objective dryness test. Lower perceived dryness was associated with higher immunological activity determined by increased levels of IgG, FLC and RF-IgA. Whereas patients with only subjective signs of dryness had lower immunological activity. Discussion: Patients' perception of dryness assessed by PSS-QoL correlates with objective measurements of salivary gland function while ESSPRI-dryness did not. Based on the PSS-QoL and objective measures of dryness two distinct groups of PSS patients could be distinguished, which may have implications in daily practice and future clinical studies.